Conditional knockout of transient receptor potential melastatin 7 in the enamel epithelium: Effects on enamel formation. (16th February 2023) - Shin, Masashi; Matsushima, Aya; Kajiya, Hiroshi; Okamoto, Fujio; Ogata, Kayoko; Oka, Kyoko; Ohshima, Hayato; Bartlett, John D.; Okabe, Koji
Abstract: Transient receptor potential melastatin 7 (TRPM7) is a unique ion channel connected to a kinase domain. We previously demonstrated that Trpm7 expression is high in mouse ameloblasts and odontoblasts, and that amelogenesis is impaired in TRPM7 kinase‐dead mice. Here, we analyzed TRPM7 function during amelogenesis in Keratin 14‐Cre;Trpm7 fl/fl conditional knockout (cKO) mice and Trpm7 knockdown cell lines. cKO mice showed lesser tooth pigmentation than control mice and broken incisor tips. Enamel calcification and microhardness were lower in cKO mice. Electron probe microanalysis (EPMA) showed that the calcium and phosphorus contents in the enamel were lower in cKO mouse than in control mice. The ameloblast layer in cKO mice showed ameloblast dysplasia at the maturation stage. The morphological defects were observed in rat SF2 cells with Trpm7 knockdown. Compared with mock transfectants, the Trpm7 knockdown cell lines showed lower levels of calcification with Alizarin Red‐positive staining and an impaired intercellular adhesion structures. These findings suggest that TRPM7 is a critical ion channel in enamel calcification for the effective morphogenesis of ameloblasts during amelogenesis.